Prevalence of Frailty in Latin America and the Caribbean: A Systematic Review and Meta-Analysis. - Fabiana Araújo Figueiredo Da Mata; Priscilla Perez da Silva Pereira; Keitty Regina Cordeiro de Andrade; Ana Claudia Morais Godoy Figueiredo; Marcus Tolentino Silva; Maurício Gomes Pereira (PLoS ONE, 2016)
Background Countries in Latin America and the Caribbean (LAC) have experienced a rapid increase in their proportion of older people. This region is marked by a high prevalence of chronic diseases and disabilities among aging adults. Frailty appears in the context of LAC negatively affecting quality of life among many older people. Aim To investigate the prevalence of frailty among community-dwelling older people in LAC through a systematic review and meta-analysis. Methods A literature search was performed in indexed databases and in the grey literature. Studies investigating the prevalence of frailty with representative samples of community-dwelling older people in Latin America and the Caribbean were retrieved. Independent investigators carried out the study selection process and the data extraction. A meta-analysis and meta-regression were performed using STATA 11 software. The systematic review was registered at the International Prospective Register of Systematic Reviews under the number CRD42014015203. Results A total of 29 studies and 43,083 individuals were included in the systematic review. The prevalence of frailty was 19.6% (95% CI: 15.4-24.3%) in the investigated region, with a range of 7.7% to 42.6% in the studies reviewed. The year of data collection influenced the heterogeneity between the studies. Conclusion Frailty is very common among older people in LAC. As a result, countries in the region need to adapt their health and social care systems to demands of an older population.